The Effect of Learning Gamelan Art on Emotional Intelligence - Jarmani Jarmani (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2022)
Teenager are increasingly confronted with emotional issues, demanding a solution such as adolescent emotional intelligence development. Traditional Indonesian music, notably Javanese gamelan, can help teenager develop emotional intelligence. People who follow a set of rules and limits undertake Javanese gamelan exercises. When practicing gamelan, the individual must hit his gamelan tool and listen to the gamelan played by his colleagues in the gamelan group to generate a harmonic gamelan sound. This study used quantitative approaches in conjunction with a sample size of 135 UWK Surabaya students. The Java Gamelan Music Exercise Intensity Scale (r = 0.848) and the Emotional Intelligence Scale (r = 0.772) are used as data-gathering instruments in the sampling technique. The product-moment correlation method was used to analyze the data, and the result was 0.550. The study's findings revealed a link between the severity of Javanese gamelan music training and emotional intelligence, with the higher the intensity of Javanese gamelan music training, the higher the emotional intelligence. The intensity variable of Javanese gamelan music training can contribute 30.25 percent to the emotional intelligence variable. In contrast, the remaining 69.75 percent is influenced by elements other than the intensity variable of Javanese gamelan music training. Beyond the intensity variables of Javanese gamelan music training, the family, non-family, physical, and psychological environments all have a role.